RECOVERING METHOD FOR GALLIUM FROM SCRAP INCLUDING GALLIUM OXIDE - NISHIYAMA YUTAKA; KIMURA ETSUJI (1989)
PURPOSE:To easily recover high purity Ga for a short time at low cost by bringing the scrap contg. gallium oxide into reaction with carbon and chlorine to chlorinate it and distillating and separating case CaCl3 which volatilizes coincidently with said chlorination. CONSTITUTION:The scrap contg. gallium oxide such as Ga2O3 gallium-gadoli- garnet (GGG), gadoli-scandium-gallium-garnet (GSGG) is preferably ground and carbon is mingled thereto. As said carbon, charcoal, etc., are used and the addition amt. thereof is preferably regulated to about 1.05-1.5 equivalence for the reduction of the oxide of rare earths, etc. Said reaction is the exothermic one and progresses automatically and actively to generate CaCl2. Said generated GaCl2 has the boiling point of 201 deg.C and volatilizes immediately. The volatilizing coarse GaCl2 is successively distillated and separated to refine. By this method, Ga is separated to recover in high purity.